Optimization of high-speed railway scheduling considering flight delays in air-rail intermodal mode - YE Binbin; HUANG Zhipeng; ZHANG Ke ³; CHENG Hong⁴ (Shenzhen da xue xue bao. Li gong ban, 2025)
The air-rail intermodal transport model combines the high speed of air travel with the high accessibility of high-speed rail to establish a comprehensive multi-dimensional transportation network. To enhance the service quality of air-rail intermodal transport and improve passengers' travel experience, this study investigates the optimization of high-speed railway scheduling under flight delay scenarios. Based on multi-objective optimization theory, a mixed-integer programming model is developed, aiming to maximize the number of successful air-rail connections and minimize train dwell times. The model comprehensively considers the fundamental train scheduling constraints, air-rail intermodal connection requirements, and passenger transfer penalty constraints. To improve computational efficiency of the model, strategies such as reducing decision variables and simplifying constraints are adopted, and a simulated annealing algorithm is used to solve the model. A case study involving Shijiazhuang Zhengding airport and the nearby high-speed railway station (Zhengding airport station) in China is conducted. The results show that the optimized train dwell times reduces 2%, while the number of successful air-rail connections increases by 2%. Sensitivity analysis of different parameters indicates that the frequency of flight delays and the width of time window for flight transfers have significant impacts on air-rail connectivity. The proposed optimization not only improves the operational efficiency of air-rail intermodal transport but also enhances passengers' travel experience, further promoting the application and development of air-rail integration in the modern transportation system.